ANALISIS PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MATA PELAJARAN ESTIMASI BIAYA KONSTRUKSI - Ar Razi Atsil Wabahey (Jurnal Ekonomi dan Bisnis, 2024)
The importance of competency in construction cost estimation highlights the crucial role of vocational education, particularly in Vocational High Schools specializing in Construction Engineering, in preparing students for the workforce. One critical skill in the construction industry is construction cost estimation, which requires a deep understanding of various project aspects and the integration of theory and practice. This study aims to evaluate the influence of the Project Based Learning (PjBL) instructional model on the subject of construction cost estimation within the Vocational Education Environment for Building Construction. The methodology employed involves a literature review, analyzing several relevant journals and articles. The comprehensive analysis results indicate the positive impact of Project Based Learning on the learning outcomes of construction cost estimation. The research findings affirm that Project Based Learning effectively enhances students' critical and creative thinking skills and the overall effectiveness of learning. Thus, Project Based Learning emerges as a relevant solution to improve student learning outcomes, particularly in the subject of Construction Cost Estimation in Vocational High Schools.